Pusat Kuliner Dan Oleh - Oleh Khas Riau Di Pekanbaru Dengan Pendekatan Arsitektur Rokan IV Koto - Junia Handayanis; Pedia Aldy; Muhammad Rijal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Pekanbaru was developing in tourism, especially in culinary and shopping souvenirs tourism. Development of culinary and shopping souvenirs in Pekanbaru growing rapidly and spread out at various corners of the city. Those things that be a reason why Pekanbaru needs a culinary and souvenirs center. Besides becoming a tourism facilities, culinary and souvenirs center expected be a education facilites for learning Malay Culture by applying one of the traditional architecture in Riau, it is Malay Architecture. One of history architecture heritage on Malay kingdom is Rokan IV Koto kingdom that located in Rokan Hulu which has different architectural form caused its geographical location. By using the architecture of Rokan IV Koto as an approach for the design, then was found a concept is “Culture Harmony”. This concept is a suitability that bind culture (culinary and souvenirs) becomes a unity by transforming Architecture of Rokan IV Koto. Culinary and Souvenirs Center is build on 3 ha area land, with area building 8019 m2. Architectural element in Architecture of Rokan IV Koto which includes region pattern and building form is transformed with dimensional transformation, addictive transformation, and subtractive transformation. The results of the transformation from the form of patterns and shapes are applied to the design of Culinary and Souvenirs Center that include zoning, mass order, outdoor planning, mass formation, indoor planning and structure.Keyword: Culinary and Souvenirs Center, Culture Harmony, Form Transformations, Architecture of Rokan IV Koto